hsa-miR-376c-3p in The Circulating Plasma is Upregulated in The Elderly Javanese Male When Compared to Their Younger Counterparts - Ana Lucia Ekowati; Zacharias Aloysius Dwi Pramono; Daniel Ardian Soeselo; Arief Budiyanto; Indwiani Astuti; Sofia Mubarika (The Indonesian Biomedical Journal, 2019)
BACKGROUND: MicroRNA (miRNA), short noncoding RNA, plays role in various physiological process such as aging through epigenetic regulation of gene expression. miRNA present intracellular as well as extracellular in body fluids. miRNA that present in blood circulatory system is often referred as circulatory miRNA (c-miRNA). A number of studies trying to identify c-miRNAs as biomarker for ageing have been reported, but majority did not yield results that corroborate one with another. This study reports the identification of a differentially expressed c-miRNAs between elderly and youth groups of individuals, the first step in tracking specific miRNAs that play role in physiologic ageing.METHODS: The miRNA expression profiles of grandfathers and grandsons from 2 Javanese families were compared to select 5 miRNA candidates with widest expression difference. The 5 candidates were subjected to validation using quantitative polymerase chain reaction (qPCR) in 11 elderly men and 9 young men of the same ethnicity to identify differentially expressed miRNA between elder and younger male groups in the represented population.RESULTS: Amongst 5 selected c-miRNA candidates, the hsa-miR-376c-3p was validated to be upregulated in the elderly group when compared to the young individuals. Bioinformatic analysis using miRTarBase 7.0, miRTargetLink Human and GeneCards® Human Gene Database suggest the involvement of hsa-miR-376c-3p in pathways relevant with cellular ageing.CONCLUSION: This study showed that hsa-miR-376c-3p in the circulating plasma to be significantly upregulated in a group of elderly Javanese males compared to their younger counterparts. The results of this study warrant further study to elucidate the specific role of hsa-miR-376c-3p in physiologic ageing mechanism.KEYWORDS: circulating, microRNA, miR-376c-3p, elderly, Javanese, male